Effect of Microgravity on Endothelial Cell Function, Angiogenesis, and Vessel Remodeling During Wound Healing - Morbidelli, Lucia; Genah, Shirley; Cialdai, Francesca (Frontiers in Bioengineering and Biotechnology, 2021)
Wound healing is a complex phenomenon that involves different cell types with various functions, i.e. keratinocytes, fibroblasts, endothelial cells, all influenced by the action of soluble mediators and rearrangement of the extracellular matrix (ECM). Physiological angiogenesis occurs in the granulation tissue during wound healing to allow oxygen and nutrient supply and waste product removal. Angiogenesis output comes from a balance between pro- and anti-angiogenic factors, which is finely regulated in a spatial and time dependent manner, in order to avoid insufficient or excessive non reparative neovascularization. The understanding of the factors and mechanisms that control angiogenesis and their change following unloading conditions (in a real or simulated space environment) will allow to optimize the tissue response in case of traumatic injury or medical intervention. The potential countermeasures under development to optimize the reparative angiogenesis that contributes to tissue healing on Earth will be discussed in relation to their exploitability in space.